Engagement of TRAIL triggers degranulation and IFNγ production in human natural killer cells. (27th June 2022) - Höfle, Johannes; Trenkner, Timo; Kleist, Nadja; Schwane, Vera; Vollmers, Sarah; Barcelona, Bryan; Niehrs, Annika; Fittje, Pia; Huynh‐Tran, Van Hung; Sauter, Jürgen; Schmidt, Alexander H; Peine, Sven; et al.
Abstract: NK cells utilize a large array of receptors to screen their surroundings for aberrant or virus‐infected cells. Given the vast diversity of receptors expressed on NK cells we seek to identify receptors involved in the recognition of HIV‐1‐infected cells. By combining an unbiased large‐scale screening approach with a functional assay, we identify TRAIL to be associated with NK cell degranulation against HIV‐1‐infected target cells. Further investigating the underlying mechanisms, we demonstrate that TRAIL is able to elicit multiple effector functions in human NK cells independent of receptor‐mediated induction of apoptosis. Direct engagement of TRAIL not only results in degranulation but also IFNγ production. Moreover, TRAIL‐mediated NK cell activation is not limited to its cognate death receptors but also decoy receptor I, adding a new perspective to the perceived regulatory role of decoy receptors in TRAIL‐mediated cytotoxicity. Based on these findings, we propose that TRAIL not only contributes to the anti‐HIV‐1 activity of NK cells but also possesses a multifunctional role beyond receptor‐mediated induction of apoptosis, acting as a regulator for the induction of different effector functions. Synopsis: This study shows that TRAIL contributes to the anti‐HIV‐1 activity of NK cells and also possesses a multifunctional role beyond receptor‐mediated induction of apoptosis, acting as a regulator for the induction of various effector functions. TRAIL contributes to the anti‐HIV‐1 activity of NK cells. In vitro HIV‐1 infection leads to upregulation of TRAIL receptors DR4 and DR5. Direct engagement of TRAIL on NK cells triggers degranulation and IFNγ production. Abstract : This study shows that TRAIL contributes to the anti‐HIV‐1 activity of NK cells and also possesses a multifunctional role beyond receptor‐mediated induction of apoptosis, acting as a regulator for the induction of various effector functions.